Current approaches to the "cultural genocide" conceptualization - Kravets, Iryna (Ukrainian Cultural Studies, 2024)
Background. In the context of increasing the amount and range of cultural genocide crimes and the absence of a legitimate international policy for its prevention and punishment, require of its research, as well as the rethinking of the concept of "genocide" in general, is being actualized. Accordingly, the purpose of the research is to analyze current approaches to "cultural genocide" conceptualization based on the primary socio-cultural concept of "genocide." Methods. The research employs theoretical methods of analysis, synthesis, comparison, and generalization, along with structural-logical and contextual methods. Results. The main reasons for the world community's attention to the study of the "cultural genocide" phenomenon are analyzed. The vectors of contemporary research into practices of cultural genocide are considered. It is clarified that the basis of such recent studies of genocidal practices has already been outlined in Raphael Lemkin's theory. The development of his theory is examined, from the proposal of the "act of barbarism" and "act of vandalism" terms to the introduction of the novel concept of "genocide." The characteristic features of genocide as a campaign aimed at the destruction of a national group are considered, as well as its key phases: the destruction of the national pattern of the oppressed group and the imposition of the national pattern of the oppressor. According to Raphael Lemkin's theory, the techniques of genocide are identified, among which particular attention is paid to the cultural ones. The newest approaches to expanding the meaning of the "genocide" concept considering contemporary cultural practices of genocide (biological, physical, and cultural components) and the introduction of a new legal term "cultural genocide" are analyzed. Conclusions. The definition of "genocide" by international legal documents, particularly the Convention on the Prevention and Punishment of the Crime of Genocide, does not represent all the components and manifestations of genocide defined by Raphael Lemkin's original socio-cultural concept. Since this inconsistency creates new cultural and legal collisions within the international space, relevant options for understanding and interpreting the "genocide" and "cultural genocide" concepts need to be found.
Keywords: genocide; international crime; cultural pattern; national identity; ethnicity; nation; cultural policy